2013
DOI: 10.1007/s00246-013-0680-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Neonates with Ebstein’s Anomaly in the Current Era

Abstract: Ebstein's anomaly is frequently detected before birth, with prenatal detection accounting for the majority of cases in the current population. This study aimed to identify the outcome variables among these infants. The medical records of 59 patients with neonatal Ebstein's anomaly managed at the Asan Medical Center between January, 2001 and June, 2012 were investigated retrospectively. In 46 cases, the diagnosis was made prenatally. Surgical/interventional procedures were performed for 27 of the analyzed patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 17 publications
2
42
1
2
Order By: Relevance
“…McElhinney et al 8 described 49 live-born neonates of whom 35 (71%) survived to hospital discharge and beyond 1 month of age. Yu et al 9 examined 59 neonates and showed a 1- and 5 year survival rate of 79% and 76%, respectively. More recently, Freud et al 15 studied perinatal mortality in fetuses with Ebstein’s anomaly or tricuspid valve dysplasia in the current era and found an overall perinatal mortality of 45%.…”
Section: Discussionmentioning
confidence: 99%
“…McElhinney et al 8 described 49 live-born neonates of whom 35 (71%) survived to hospital discharge and beyond 1 month of age. Yu et al 9 examined 59 neonates and showed a 1- and 5 year survival rate of 79% and 76%, respectively. More recently, Freud et al 15 studied perinatal mortality in fetuses with Ebstein’s anomaly or tricuspid valve dysplasia in the current era and found an overall perinatal mortality of 45%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from our center has described the management of 59 neonates with an Ebstein anomaly that had been treated in our division of pediatric cardiology between 2001 and 2012 [7]. In contrast to earlier reports that the majority of neonatal Ebstein anomalies are not diagnosed in the prenatal period [9,10], 46 of the patients (78%) at our center had been prenatally diagnosed with this condition [7]. Two babies in this series died immediately after birth, and among the remaining 57 neonates with an Ebstein anomaly, there were only 2 type-D cases (3.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Type A is designated as an adherence of the septal and posterior leaflets without a restriction of the functional right ventricle volume; type B means that the right ventricle has atrialized with a normal anterior leaflet; type C refers to cases with a stenotic anterior leaflet; and type D cases manifest with an almost complete atrialization of the ventricle, with the exception of a small infundibular component. Although the precise prevalence of each type of Ebstein anomaly has not been investigated, it is assumed that type D accounts for 3.5% to 8% of cases [7,12] and also that the prenatal diagnosis of type-D is rarer. In type-D cases, all of the leaflet tissue, even the anterior parts, is attached to the right ventricular wall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations